2014
DOI: 10.3389/fncel.2014.00267
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of TRPM4 and TRPM5 nonselective cation channels to the slow afterdepolarization in mouse prefrontal cortex neurons

Abstract: In certain neurons from different brain regions, a brief burst of action potentials can activate a slow afterdepolarization (sADP) in the presence of muscarinic acetylcholine receptor agonists. The sADP, if suprathreshold, can contribute to persistent non-accommodating firing in some of these neurons. Previous studies have characterized a Ca2+-activated non-selective cation (CAN) current (ICAN) that is thought to underlie the sADP. ICAN depends on muscarinic receptor stimulation and exhibits a dependence on ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 58 publications
3
47
0
Order By: Relevance
“…The primary evidence for an indirect pathway is the sensitivity of persistent firing to chelation of Ca 2+ ions (Lei et al 2014, Rahman & Berger 2011). Simple biophysical mechanisms, such as triggering regenerative inward Ca 2+ or Na + currents, are triggered directly by depolarizing stimuli and therefore should not be abolished by blockade of the intracellular signaling function of Ca 2+ ions.…”
Section: Cell-autonomous Biophysical Mechanisms For Generating Persismentioning
confidence: 99%
See 2 more Smart Citations
“…The primary evidence for an indirect pathway is the sensitivity of persistent firing to chelation of Ca 2+ ions (Lei et al 2014, Rahman & Berger 2011). Simple biophysical mechanisms, such as triggering regenerative inward Ca 2+ or Na + currents, are triggered directly by depolarizing stimuli and therefore should not be abolished by blockade of the intracellular signaling function of Ca 2+ ions.…”
Section: Cell-autonomous Biophysical Mechanisms For Generating Persismentioning
confidence: 99%
“…Although the molecular identity of the ion channel mediating this response is unknown, it appears to be gated by Ca 2+ (or Ca 2+ ions bound to an accessory protein), is permeable to Na + and Ca 2+ , and is sensitive to flufenamic acid (FFA; Haj-Dahmane & Andrade 1999, Lei et al 2014, Rahman & Berger 2011, Tahvildari et al 2008, Zhang et al 2011), a nonsteroidal anti-inflammatory agent. Several groups have hypothesized that a subtype of transient receptor potential (TRP) channels may mediate I CAN responses, based on pharmacological studies (Lei et al 2014, Reboreda et al 2011, Petersson & Fransén 2012) and tests of peptides that interfere with TRP channel function (Yan et al 2009, Zhang et al 2011). However, thus far no direct evidence has demonstrated that persistent firing and the associated afterdepolarization response are abolished in TRP channel knockout animals [although Lei et al (2014) found partial blockade in TRPM5 knockout mice].…”
Section: Cell-autonomous Biophysical Mechanisms For Generating Persismentioning
confidence: 99%
See 1 more Smart Citation
“…; Lei et al. ). Future experiments should focus on rigorously ruling out calcium currents involved in AHP shortening via highly selectively calcium channel blockers.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, besides TRPC, other subfamily member of TRP channels, that are expressed in the brain (Sawamura, Shirakawa, Nakagawa, Mori, & Kaneko, ), could underlie persistent activity in cortical neurons. For instance, the TRP melastatin 5 channel (TRPM5) contributes importantly to the sADP in the mouse prefrontal cortex (Lei et al, ). By examining animals in which TRPM4 and TRPM5 channels were genetically deleted either alone or in combination this study further showed that TRPM5 but not TRPM4 channels are involved in the generation of the sADP in LV neurons.…”
Section: Discussionmentioning
confidence: 99%